The College of American Pathologists Guidelines for Whole Slide Imaging Validation are Feasible for Pediatric Pathology: A Pediatric Pathology Practice Experience. (March 2015) - Arnold, Michael A.; Chenever, Emily; Baker, Peter B.; Boué, Daniel R.; Fung, Bonita; Hammond, Sue; Hendrickson, Brett W.; Kahwash, Samir B.; Pierson, Christopher R.; Prasad, Vinay; Nicol, Kathleen K.; Barr, Thomas
Whole slide imaging (WSI) is rapidly transforming educational and diagnostic pathology services. Recently, the College of American Pathologists Pathology and Laboratory Quality Center (CAP-PLQC) published recommended guidelines for validating diagnostic WSI. We prospectively evaluated the guidelines to determine their utility in validating pediatric surgical pathology and cytopathology specimens. Our validation included varied pediatric specimen types, including complex or less common diagnoses, in accordance with the guidelines. We completed WSI review of 60 surgical pathology cases and attempted WSI review of 21 cytopathology cases. For surgical pathology cases, WSI diagnoses were highly concordant with glass slide diagnoses; a discordant diagnosis was observed in 1 of 60 cases (98.3% concordance). We found that nucleated red blood cells and eosinophilic granular bodies represented specific challenges to WSI review of pediatric specimens. Cytology specimens were more frequently discordant or failed for technical reasons, with overall concordance of 66.7%. Review of pediatric cytopathology specimens will likely require image capture in multiple focal planes. This study is the first to specifically evaluate WSI review for pediatric specimens and demonstrates that specimens representing the spectrum of pediatric surgical pathology practice can be reviewed using WSI. Our application of the proposed CAP-PLQC guidelines to pediatric surgical pathology specimens is, to our knowledge, the first prospective implementation of the CAP-PLQC guidelines.